The Influence of the Addition of Rosehip Powder to Wheat Flour on the Dough Farinographic Properties and Bread Physico-Chemical Characteristics - Nicoleta Vartolomei; Maria Turtoi (Applied Sciences, 2021)
An in-depth analysis of wheat flour (WF) substituted with 0.5–2.5% rosehip powder (Rp) concerning the proximate composition, dough farinographic properties, and bread physico-chemical characteristics was performed. The purpose of this study was to investigate whether the use of Rp as a natural alternative for synthetic ascorbic acid in breadmaking was appropriate. A sample of wheat flour with an ascorbic acid addition of 2 mg/100 g was also used. Rp showed higher ash, carbohydrates, and fibre content, as well as lower moisture and protein content compared to wheat flour, and a vitamin C content of 420 ± 16.09 mg/100 g. A proximate composition analysis revealed a decrease in moisture, protein, and wet gluten, and an increase in ash, carbohydrates, and fibres for the flour mixtures compared with WF. Farinographic properties were positively influenced by the Rp addition and the high fibre content in the flour mixtures. Water absorption increased from 58.20% (WF) to 61.90% (2.5% Rp). Dough stability increased for the 0.5–1.0% Rp addition, then slightly decreased. The physico-chemical properties of bread prepared from flour mixtures showed a significant increase in height: 100.10 ± 0.14 mm (WF)–115.50 ± 0.14 mm (1.5% Rp), specific volume: 142.82 cm3/100 g (WF)–174.46 cm3/100 g (1.5% Rp), moisture: 41.81 ± 0.40% (WF)–43.92 ± 0.15% (2.0% Rp), and porosity: 87.75 ± 1.06% (WF)–89.40 ± 0.57% (2.5% Rp). The results indicated that the Rp used in breadmaking to replace synthetic ascorbic acid could be suitable.